2018
DOI: 10.1186/s13567-018-0613-z
|View full text |Cite
|
Sign up to set email alerts
|

Global discovery of small RNAs in the fish pathogen Edwardsiella piscicida: key regulator of adversity and pathogenicity

Abstract: Recently, bacterial small RNA (sRNA) has been shown to be involved as a key regulator in stress responses. sRNAs of Edwardsiella piscicida, an important aquatic pathogen, are not well characterized to date. In this study, using RNA-seq technology, we globally found and identified sRNA candidates expressed from E. piscicida grown in normal LB medium, acid pressure, iron deficiency stress, and oxidation pressure. A total of 148 sRNAs were found, including 19 previously annotated sRNAs and 129 novel sRNA candidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…The regulation of esrB links the stress conditions and virulence expression level during the progression of infection in E. piscicida and other phylogenetically related pathogens such as Salmonella species [89]. Hfq is another global regulator of an mRNA/sRNA chaperon associated with pathogenesis and interacts with~49 sRNA in E. piscicida; there were~148 sRNAs including 129 novel sRNAs that were associated with regulation of adversity adaptation and pathogenicity [90]. Although the distinct sRNAs and targeted mRNAs remain unknown, preliminary data in E. pisicicida suggested that Hfq is involved in T3SS/T6SS expression and in vivo pathogenesis (Wang QY et al, unpublished communication).…”
Section: Virulence Regulators and Crosstalk Regulation Of T3ss/t6ssmentioning
confidence: 99%
“…The regulation of esrB links the stress conditions and virulence expression level during the progression of infection in E. piscicida and other phylogenetically related pathogens such as Salmonella species [89]. Hfq is another global regulator of an mRNA/sRNA chaperon associated with pathogenesis and interacts with~49 sRNA in E. piscicida; there were~148 sRNAs including 129 novel sRNAs that were associated with regulation of adversity adaptation and pathogenicity [90]. Although the distinct sRNAs and targeted mRNAs remain unknown, preliminary data in E. pisicicida suggested that Hfq is involved in T3SS/T6SS expression and in vivo pathogenesis (Wang QY et al, unpublished communication).…”
Section: Virulence Regulators and Crosstalk Regulation Of T3ss/t6ssmentioning
confidence: 99%
“…The interaction E . piscicida and host cells were studied as reported previously (Du et al, 2018). Briefly, FG cells and Hela cells were cultured to a single layer in a 48‐well cell plate and infected with TX01, TX01Δ rat A, TX01Δ rat AB, TX01Δ rat AC and TX01Δ rat ABC strains at a multiplicity of infection (MOI) of 50: 1.…”
Section: Methodsmentioning
confidence: 99%
“…The interaction of E . tarda and host cells was studied as reported previously [ 38 ]. Briefly, E. tarda TX01, TX01Δ cadA , TX01Δ cadB , TX01Δ cadBA , TX01Δ cadA C, and TX01Δ cadB C strains were grown in LB broth at 30 °C and then transferred into DMEM without shaking until the optical density at 600 nm reached 1.0.…”
Section: Methodsmentioning
confidence: 99%